Study of the rooting capacity of eleven pomegranate (Punica granatum L.) clones, using plastic to cover the soil - Melgarejo P.; Martínez J.; Martínez J.J.; Martínez Valero R.; Amorós A. (Production, processing and marketing of pomegranate in the Mediterranean region: Advances in research and technology, 2000)
In a continuation of our studies of the rooting capacity of different pomegranate clones propagated by taking hardwood cuttings, we studied the results obtained the previous year and those obtained by improving cultivation techniques using a polyethylene film, which saves a lot of water and cuts labour cost during the rooting period. Rooting capacity increased with the technique and labour costs of producing rooted cuttings were cut by 37 per cent.
Symposium on 'Production, processing and marketing of pomegranate in the Mediterranean region: Advances in research and technology', 1998/10/15-17, Orihuela (Spain)